1987
DOI: 10.1111/j.1365-2125.1987.tb03132.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on spontaneous improvement in patients with podagra: implications for therapeutic trials of non‐steroidal anti‐inflammatory drugs.

Abstract: 1 The natural history of acute gouty arthritis was studied in 11 volunteers with podagra. 2 Two patients withdrew from the study on day 4 because of severe persistent pain. Of the remaining patients all showed some improvement in pain by day 5 and in swelling by day 7. Tenderness improved in seven patients by day 7 but two continued to experience the same amount of discomfort as at trial entry. In spite of these improvements only three patients noted resolution of their pain during the study period. 3 These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 3 publications
0
24
0
1
Order By: Relevance
“…This was based on guidance provided by the findings of a study by Bellamy et al (32), showing that resolution of pain is very unlikely to occur within a 4-day period without the use of effective medication. This study serves as a reference for clinical trials in acute gout because placebo-controlled trials are not considered ethical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was based on guidance provided by the findings of a study by Bellamy et al (32), showing that resolution of pain is very unlikely to occur within a 4-day period without the use of effective medication. This study serves as a reference for clinical trials in acute gout because placebo-controlled trials are not considered ethical.…”
Section: Discussionmentioning
confidence: 99%
“…Comparability was declared if the 95% confidence interval (95% CI) for the between-group difference in the patient's assessment of pain (days 2-5 [primary] and days 2-8 [secondary]) fell within the prespecified comparability bounds of Ϯ0.5 points on the 0-4-point Likert scale. An observed mean change of Ͼ1.46 points for the patient's assessment of pain was prespecified to define a clinical response to indomethacin, based on previously published guidance (31,32), since inclusion of a placebo group was deemed unethical in this painful condition.…”
Section: Methodsmentioning
confidence: 99%
“…It can also be seen that the response in Blue- Bluestone (1982), Murphy (1979), Ahem et al (1987 and Ruotsi & Vainio (1978) show at best only a 12% improvement over placebo, and a 27% improvement over the untreated group of Bellamy et al (1987). This may reflect factors of patient selection, but may also poorly reflect on the capacity of treatment (in some instances) to achieve the desired result; namely the swift relief of pain.…”
mentioning
confidence: 90%
“…Pathology, imaging and intervention studies have demonstrated that the clinical manifestations of gout occur because of the host inflammatory response to deposited MSU crystals [8][9][10][11][12][13] , exemplified by acute gout flares 10 . The acute flares characteristically present as an exquisitely painful inflammatory arthritis 14 , which leads to severe limitation of activity, poor quality of life and work disability 15 . These events are highly consequential to the health-related quality of life of affected patients, and also have added socioeconomic effects 16 .…”
Section: Rationale For the G-can Positionmentioning
confidence: 99%